Subcutaneous Sterile Water Injection for Labor Pain: A Randomized Controlled Trial - Rai, R; Uprety, DK; Pradhan, T; Bhattarai, BK; Acharya, S (Nepal Journal of Obstetrics and Gynaecology, 2014)
Aims: This study was done to evaluate the effectiveness of subcutaneous injection of sterile water compared with placebo in reduction of labor pain. Methods: Two hundred and forty pregnant women at term planned for normal vaginal delivery during the first stage of labor were randomized to receive either subcutaneous injection of sterile water (study group, n=120) or normal saline as placebo (control group, n=120) at painful point in lumbosacral region. Pain score was measured before and 10, 45 and 90 minutes after the injections. Main outcome measured was reduction of low back labor pain using visual analogue scale. Results: The mean pain score was equal in both groups prior to the injection. The pain scores were significantly lower among the intervention group compared to the control group at 10, 45, 90 minutes after injection. There was no difference between the two groups with regard to rate of instrumental delivery, cesarean rate and neonatal outcome. Conclusions: The subcutaneous injection of sterile water administered at painful point in lumbosacral area was effective in reducing low back labor pain during labor. DOI: http://dx.doi.org/10.3126/njog.v8i2.9777